Literature Review ; Efektifitas Penggunaan Virtual Reality Untuk Meningkatkan Kemampuan Softskill dan Capaian Kompetensi Mahasiswa Pada Mata Kuliah Keperawatan Jiwa - falah, fakhriatul (Jurnal Teknologi informasi dan Ilmu Komputer, 2025)
Anxiety during psychiatric nursing practice can affect their knowledge, confidence, and clinical skills which have an impact on learning outcomes. However, in reality, after dealing directly with psychiatric patients, students are unable to apply communication and experience decreased self-confidence when interacting with psychiatric patients. Therefore, an innovative strategy is needed to develop students' soft skills in interacting with psychiatric patients using virtual reality media. This study was conducted by conducting a literature review to examine the effectiveness of using virtual reality in improving students' softskill and learning outcome achievement in psychiatric nursing courses. Based on a systematic analysis of 12 articles, it was found that virtual reality can be used as an effective learning media to softskill  skills dan learning outcomes  in nursing students.